Microbial fertilizer from PK rocks on lettuce nutrients and soil attributes in consecutive crops - Oliveira, Wagner da Silva; Stamford, Newton Pereira; Silva, Emmanuella Vila Nova da; Arnaud, Thatiana Stamford; Izquierdo, Carlos Garcia; Hernández, Teresa (Pesquisa Agropecuaria Brasileira, 2021)
The objective of this work was to evaluate the effect of a microbial fertilizer, produced from phosphate and potassic rocks and earthworm compost, as an alternative to conventional fertilizers, on lettuce (Lactuca sativa) nutrients and soil attributes. The experiment was conducted in consecutive cycles (30 and 60 days) in a soil from the Lorca region, in the municipality of Murcia, Spain. The fertilization treatments were: conventional fertilizer, 100% of the recommended rate (RR); microbial fertilizer, 50% of the RR (5 Mg ha-1); microbial fertilizer, 100% of the RR (10 Mg ha-1); microbial fertilizer, 150% of the RR (15 Mg ha-1); and control, without N-P2O5-K2O fertilization. The microbial fertilizers applied at 100 and 150% of the RR showed significant and positive effects, as well as the best results for plant characteristics. The microbial fertilizer increased total N and available P and K compared with the conventional fertilizer. A residual effect was observed in the successive cycle. The effectiveness of the microbial fertilizer shows it is a viable alternative to conventional fertilizers, with positive effects on plant productivity and soil attributes.